A simple means of producing highly transparent graphene on sapphire using chemical vapor deposition on a copper catalyst - Anemone, Gloria; Climent-Pascual, Esteban; Al Taleb, Amjad; Yu, Hak Ki; Jiménez-Villacorta, Felix; Prieto, Carlos; Wodtke, Alec M.; De Andrés, Alicia; Farías, Daniel (Carbon, 2018)
Chemical vapor deposition (CVD) is one of the best ways to scalably grow low cost, high quality graphene on metal substrates; unfortunately, it not ideal for producing graphene on dielectric substrates. Here, we demontrate production of a high quality graphene layer on Sapphire using CVD with a copper catalyst. The catalyst consists of a thin copper film grown epitaxially on α-Al2O3 (0001). After CVD growth of Graphene, the copper can be removed by simple evaporation in the presence of a carbon source (C2H4). We characterized the resulting graphene layer using Raman spectroscopy, atomic force microscopy (AFM), optical transmission and helium atom scattering (HAS). The sample exhibited a reduced Raman D peak and an excellent 2D to G ratio. AFM and HAS show large graphene domains over a macroscopic region. We measured >86% transparency over the visible spectrum.
Keywords: Chemical vapor depositions (CVD); Cvd-growth of graphene; Dielectric substrates; Helium atom scattering; Macroscopic regions; Thin copper films; Transparent graphene; Visible spectra